Prognostic Value of Myocardial Blush Grade in ST-elevation MI: A Systematic Review and Meta-analysis - Patrick Vera Cruz; Patricio Palmes; Nadine Bacalangco (Interventional Cardiology: Reviews, Research, Resources)
Background: Ineffective myocardial perfusion despite angiographic success after angioplasty occurs frequently and is associated with an increased risk of mortality. Hence, this study determined whether myocardial perfusion measured by myocardial blush grade (MBG) identifies ST-elevation MI (STEMI) patients at high risk for poor outcomes after successful angioplasty. Methods: The search employed strategies designed for research databases. An article was eligible if it included adults who underwent coronary angioplasty for STEMI, post-angioplasty MBG was assessed, and mortality or major adverse cardiovascular events (MACE) were determined. Risk for bias was assessed using the Quality In Prognosis Studies tool and forest plots in a Mantel-Haenszel fixed effects model were created using RevMan5.4. Results/discussion: Eight observational studies with an overall low risk of bias were included, involving 8,044 patients. MBG 0/1 with no to poor myocardial perfusion had a negative prognostic value for mortality (OR 2.68; 95% CI [2.22–3.23]) and MACE (OR 1.20; 95% CI [1.01–1.41]). Furthermore, MBG 2 with moderate myocardial perfusion and MBG 3 with normal myocardial perfusion were associated with increased survival with a logHR of 0.47 (95% CI [0.43–0.52]) and 0.20 percutaneous coronary intervention (95% CI [0.18–0.23]). These results imply MBG is a useful prognostic marker for STEMI patients. Conclusion: MBG 0/1 after primary angioplasty is a strong negative prognostic marker for long-term all-cause mortality and MACE among STEMI patients, and a post-primary angioplasty MBG of 2 or 3 is a robust prognostic marker for long-term survival.